The Importance of Hematological and Demographic Characteristics in the Course of COVID-19 Pneumonia - Senol, Arzu; Gundag, Omur; Balin, Safak Ozer; Toraman, Zulal Asci; Gul, Yeliz; Yildirim, Ali (Bilimsel Tip Yayinevi, 2021)
Introduction: COVID-19 is a rapidly progressive viral disease and early diagnosis is important. We aimed to analyze the hematological parameters that can assist in early detection of severe COVID-19 pneumonia and to determine the significance of demographic characteristics and laboratory parameters in predicting progression to severe disease in mild-to-moderate COVID-19 pneumonia. Materials and Methods: This study included 336 patients with COVID-19 pneumonia. Patients' demographic data and laboratory findings were obtained retrospectively. The patients were divided into two groups: mild-to-moderate and severe pneumonia. Results: Of 336, 152 patients had mild-to-moderate and 184 had severe COVID-19 pneumonia. White blood cell, aspartate aminotransferase, fibrinogen, D-dimer, procalcitonin, ferritin, troponin, C-reactive protein levels, systemic inflammatory index, and absolute neutrophil (N) count, as well as N-to-lymphocyte (L), monocyte (M)-to-L, and platelet-to-L ratios were significantly higher in severe pneumonia than mild-to-moderate ones. Albumin level, absolute L and M count, and erythrocyte distribution width were significantly lower in severe pneumonia. The most common comorbidities were hypertension, diabetes, chronic obstructive pulmonary disease. Conclusion: Findings of this study suggest that some laboratory parameters have prrognostic value in COVID-19 patients are beneficial and frequent follow-ups of selected laboratory parameters can play a key role, especially in patients with comorbidities and advanced age due to the increased risk of severity.
Keywords: COVID-19 pneumonia; Hematological parameters; Demographic characteristics; Comorbidities